THE INFLUENCE OF SELECTED FACTORS ON THE SALARY OF EMPLOYEES IN THE ZILINA REGION - Svabova, Lucia (Doprava a spoje, 2012)
The paper deals with differentiation of wages of employees in the selected region of Slovakia, which was the region Zilina. The main aim of the paper, based on theoretical knowledge and the obtained data, was to compare the average monthly gross salaries of employees in the selected region with average nationwide salaries and to characterize their causes. The paper analyzes and interprets the research results, using the statistical techniques and methods of comparison. The secondary objective of research was to compare the salaries of employees by age, gender and the degree of education. We compare the differences in the salaries in the region Zilina and characterize the possible causes of these differences. The research results revealed that average salaries in the region Zilina are affected by age, education and the gender of employees